2011
DOI: 10.1007/s12524-011-0070-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Coherence Based Technique for Near-Real Time Sea-Ice Identification from Scatterometer Data

Abstract: The identification of sea-ice has frequently been cited as one of the most important tasks for deriving the sea-ice parameters and to avoid erroneous retrieval of wind vector over sea-ice infested oceans using space-borne scatterometer data. Discrimination between sea-ice and ocean is ambiguous under the high wind and/or thin/scattered ice conditions. The pre-launch technique developed for Oceansat-2, utilizes the dual-polarized QuikSCAT scatterometer data by using the spatio-temporal coherence properties of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…One is based on the microwave backscattering characteristics of sea ice, including the backscattering powers of the horizontal and vertical polarization. Sea ice and sea water recognition was first carried out using C-band data [12,18,19], and then the Ku-band was demonstrated to be applicable for recognizing sea ice and sea water [20,21]. Recognition accuracies achieved 90% [22].…”
Section: Introductionmentioning
confidence: 99%
“…One is based on the microwave backscattering characteristics of sea ice, including the backscattering powers of the horizontal and vertical polarization. Sea ice and sea water recognition was first carried out using C-band data [12,18,19], and then the Ku-band was demonstrated to be applicable for recognizing sea ice and sea water [20,21]. Recognition accuracies achieved 90% [22].…”
Section: Introductionmentioning
confidence: 99%
“…Discrimination between sea-ice and ocean is ambiguous in the Scaterrometer observations under the high wind and/ or thin/scattered ice conditions. Oza et al (2011b) developed an algorithm to distinguish ocean winds from the sea ice in both the hemispheres using spatiotemporal coherence techniques, in addition to backscatter coefficient and the Active Polarization Ratio (API). These authors found that the threshold Antarctic sea ice thickness has also been retrieved by using Ice Cloud and land Elevation satellite (ICEsat) elevation measurements to retrieve sea-ice (with snow cover) freeboard in the Weddell Sea Antarctica (Kern and Spreen, 2015).…”
Section: Development Of Techniques For Sea Ice Characterizationmentioning
confidence: 99%
“…Discrimination between sea-ice and ocean is ambiguous in the Scaterrometer observations under the high wind and/ or thin/scattered ice conditions. Oza et al (2011b) developed an algorithm to distinguish ocean winds from the sea ice in both the hemispheres using spatiotemporal coherence techniques, in addition to backscatter coefficient and the Active Polarization Ratio (API). These authors found that the threshold…”
Section: Development Of Techniques For Sea Ice Characterizationmentioning
confidence: 99%
“…Automatic identification of sea-ice edge and its validation using enhanced resolution QuikSCAT data has been carried out byHaarpaintner et al (2004). As mentioned earlier, Scatterometer data has shown its potential in delineating the sea ice extent(Oza et al, 2010d;Rivas and Stoffelen, 2011;Rivas et al, 2018;Haarpaintner et al, 2004) Li et al (2016). have demonstrated the potential of Chinese HY-2A Scatterometer for sea ice monitoring Lindell and Long (2016).…”
mentioning
confidence: 98%
“…An attempt was also made to estimate the sea ice concentration using OSCAT (Ku-band) and ASCAT (C-band) Scatterometer data(Singh et al 2014c). In the study carried out byOza et al (2010d), various values of Active Polarisation Ratio (APR) ranging from (-0.01) to (-0.04) at 0.005 interval were used to arrive at the optimum APR threshold for sea ice detection in the Arctic and the Antarctic regions. The recent work carried out by SAC using SCATSAT-1 Scatterometer is shown in Figure3.4 Oza et al (2009a;2009c, 2010c.…”
mentioning
confidence: 99%